Implementasi Liniear Congruential Generator Pada Pembangkitan Inizialization Vector Pada Kriptografi CBC Sederhana - Riski, Sari Kurnia; Tommy, Tommy; Budiman, Arief (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2023)
In this era of increasingly advanced technology, data security is very important in maintaining the confidentiality of information, especially those containing sensitive information whose contents should only be known by the entitled party, especially if the delivery is made through a public network, if the data is not secured first. , will be very easy to be tapped and the contents of the information known by parties who do not have the authority. One way that is used for data security is to use a cryptographic system, namely by encoding or keying the information content using a data locking algorithm method. Here this author will discuss about generating IV using the LCG algorithm are combined by XORing everyption method in simple CBC cryptography where these two algorithm are combined by XORing every bit that exists with the key or block provided. Aims to produce plaintext that has been convertd into ciphertext or secret data. Keywords : data security, cryptographic algorithm lcg, xor cipher, simple cbc method.